Novel fluctuation reduction procedure for nuclear reactivity calculations based on the discrete fourier transform method (2019)
A new method for calculating nuclear reactivity based on the Discrete Fourier Transform (DFT) – with two filters: a first-order delay low-pass filter and a Savitzky-Golay filter – is presented. The reactivity is calculated from an integrodifferential equation known as the inverse point kinetic equation, which contains the history of neutron population density. The new method can be understood as a convolution between the neutron population density signal and the response to the characteristic impulse of a linear system. The proposed method is based on the discrete Fourier transform (DFT) that performs a circular convolution. The fast Fourier transform algorithm (FFT) with the zero-padding technique is implemented to reduce the computational cost